Frontispiz: Long‐Lived Charge‐Transfer State in Spiro Compact Electron Donor–Acceptor Dyads Based on Pyromellitimide‐Derived Rhodamine: Charge Transfer Dynamics and Electron Spin Polarization. (8th August 2022) - Chen, Xi; Sukhanov, Andrey A.; Yan, Yuxin; Bese, Damla; Bese, Cagri; Zhao, Jianzhang; Voronkova, Violeta K.; Barbon, Antonio; Yaglioglu, Halime Gul
Abstract : Elektronentransfer . In ihrem Forschungsartikel (e202203758 ) untersuchen Jianzhang Zhao et al. den langlebigen Ladungstransferzustand in Spiro‐Donor‐Akzeptor‐Dyaden auf der Grundlage von Pyromellitimid‐abgeleitetem Rhodamin.